Aging and Learning in a Non-Western Culture: The Case of Malaysia - Muhamad Mazanah; Sharan B. Merriam (Adult Education Research Conference, 2000)
A case study on older Malaysian men and women revealed that from their perspective, aging is seamless and a period of contentment. They are concerned about their health, spiritual, and community. They learn informally to meet the changing demands of their life. The learning is shaped by their cultural value.